2000
DOI: 10.4049/jimmunol.165.11.6504
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Onset of Inflammation in Protease-Activated Receptor-2-Deficient Mice

Abstract: Endothelial surface expression of P-selectin and subsequent leukocyte rolling in venules can be induced by mast cell-derived histamine and binding of thrombin to protease-activated receptor-1 (PAR1). We hypothesized that activation of endothelial PAR2 by mast cell tryptase or other proteases also contributes to inflammatory responses. Leukocyte rolling flux and rolling velocity were assessed by intravital microscopy of the cremaster muscles of wild-type mice following perivenular micropipette injections of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
209
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(218 citation statements)
references
References 47 publications
8
209
0
1
Order By: Relevance
“…To our knowledge, our results provide the first evidence that PAR2 plays an important role in mediating the infiltration of leukocytes in the acute phases of allergic inflammation of the airways. In support of our results, perivascular application of PAR2 agonists promotes the rolling and firm adhesion of lymphocytes in rat mesenteric vessels (37), and surgically induced lymphocyte rolling and adhesion is diminished in PAR2ko mice different from those used in the current investigation (38). The intraplantar administration of PAR2 agonists in rats also causes granulocyte infiltration (32).…”
Section: Par2 Mediates Allergic Inflammation Of the Airwayssupporting
confidence: 85%
“…To our knowledge, our results provide the first evidence that PAR2 plays an important role in mediating the infiltration of leukocytes in the acute phases of allergic inflammation of the airways. In support of our results, perivascular application of PAR2 agonists promotes the rolling and firm adhesion of lymphocytes in rat mesenteric vessels (37), and surgically induced lymphocyte rolling and adhesion is diminished in PAR2ko mice different from those used in the current investigation (38). The intraplantar administration of PAR2 agonists in rats also causes granulocyte infiltration (32).…”
Section: Par2 Mediates Allergic Inflammation Of the Airwayssupporting
confidence: 85%
“…We also identify the molecular targets whose down-regulation results in this effect. It is also important to note that several recent animal studies have demonstrated that fXa and thrombin, as well as PAR1 and -2, can mediate inflammatory responses in vivo (55)(56)(57). Although this study focuses on a coagulation protease, it is likely that other proteases that are capable of cleaving PAR1 or -2, such as proteases originating from monocytes or neutrophils, when costimulated with inflammatory cytokines could elicit similar endothelial activation (TF and E-selectin induction).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Lindner and colleagues (19) have reported that although the inflammatory response to surgical trauma was delayed in PAR-2-deficient mice, this inhibition was not long-lasting. The substantial inhibition of adjuvant-induced arthritis we observed in the PAR-2 -/-group, coupled with the failure of NK 1 receptor deletion to inhibit adjuvant arthritis (20), suggests that PAR-2 may mediate chronic joint inflammation by non-neurogenic mediators, perhaps via the cytokine cascade.…”
Section: Discussionmentioning
confidence: 99%